Restoring the gate: laparoscopic Nissen fundoplication significantly elevates lower esophageal sphincter pressure and alleviates GERD symptoms - Dhanorkar, Tanay; Shaikh, Aftab; Akotkar, Shubham; Menon, Balakrishna (International Surgery Journal, 2026)
Background: Gastroesophageal reflux disease (GERD) is a highly prevalent condition with significant quality-of-life implications. Laparoscopic fundoplication is the established surgical standard of care, yet quantitative manometric data from Indian tertiary care centers remain sparse. To compare preoperative and postoperative lower esophageal sphincter (LES) pressure in patients undergoing laparoscopic Nissen fundoplication and to correlate manometric changes with symptomatic improvement. Methods: An observational study of 45 adults who underwent laparoscopic Nissen fundoplication (January–December 2023) at a tertiary care center. High-resolution esophageal manometry (HRM) was performed within one month preoperatively and within three months postoperatively. Symptom severity was assessed using the validated GERD-Q questionnaire. Statistical analysis employed the Wilcoxon Signed-Rank Test (p≤0.05 considered significant). Results: Mean LES pressure increased significantly from 10.80±1.78 mmHg preoperatively to 16.77±3.77 mmHg postoperatively (median: 10.11 → 15.80 mmHg, p<0.05). The GERD-Q score improved from 9.96±2.35 to 6.76±1.37 (p<0.05). Of 45 patients, 43 (95.6%) demonstrated LES pressure augmentation and 42 (93.3%) reported symptomatic improvement. The overall complication rate was 11.1%, all managed conservatively. Conclusions: Laparoscopic Nissen fundoplication produces a statistically significant and clinically meaningful increase in LES resting pressure alongside significant symptomatic relief. These findings from an Indian tertiary care centre corroborate international data and support fundoplication as a safe, effective intervention for GERD refractory to medical therapy.